Incorporating reaction-rate dependence in reaction-front models of wellbore-cement/carbonated-brine systems. (April 2017) - Iyer, Jaisree; Walsh, Stuart D.C.; Hao, Yue; Carroll, Susan A.
Abstract : Graphical abstract: Abstract : Highlights: Extended model to predict calcite precipitation within fractures. Pressure control facilitates sealing of fractures through calcite precipitation. Residence time and fracture aperture determine fracture sealing. Mechanical deformation facilitates sealing of fractures at lower residence times. Prior leaching of calcium from the cement may influence sealing behavior. Abstract: Contact between wellbore cement and carbonated brine produces reaction zones that alter the cement's chemical composition and its mechanical properties. The reaction zones have profound implications on the ability of wellbore cement to serve as a seal to prevent the flow of carbonated brine. Under certain circumstances, the reactions may cause resealing of leakage pathways within the cement or at cement-interfaces; either due to fracture closure in response to mechanical weakening or due to the precipitation of calcium carbonate within the fracture. In prior work, we showed how mechanical sealing can be simulated using a diffusion-controlled reaction-front model that links the growth of the cement reaction zones to the mechanical response of the fracture. Here, we describe how such models may be extended to account for the effects of the calcite reaction-rate. We discuss how the relative rates of reaction and diffusion within the cement affect the precipitation of calcium carbonate within narrow leakage pathways, and how such behavior relates to the formation of characteristic reaction modes in the direction of flow. In addition, we compare the relative impact of precipitation and mechanical deformation on fracture sealing for a range of flow conditions and fracture apertures. We conclude by considering how the prior leaching of calcium from cement may influence the sealing behavior of fractures, and the implication of prior leaching on the ability of laboratory tests to predict long-term sealing.